High concentrations of polyethylene microplastics restrain the growth of Cinnamomum camphora seedling by reducing soil water holding capacity - Run Yang; Jinping Wang; Huanying Fang; Jinwen Xia; Guomin Huang; Rongzhen Huang; Hong Zhang; Liqin Zhu; Lichao Zhang; Jihong Yuan (Ecotoxicology and Environmental Safety)
The accumulation of microplastics (MPs) in soils due to anthropogenic activities affects the growth and development of plants and thereby endangering the diversity and function of ecosystems. Although there is an increasing number of studies exploring the effects of MPs on plants in recent days, most of them focus on crops only. However, few studies have been conducted on woody plants that play a prominent role in ecosystems, while crucial edaphic factors which potentially restrain plant growth in MP-contaminated soils are yet to be revealed. In the current study, a 6-month pot experiment was conducted to investigate the inhibitory effect of soil polyethylene microplastics (PE-MPs) (average size of 6.5 µm) with increasing concentrations (0, 0.1 %, 0.5 %, 1 %, and 2 % w/w) on the growth of Cinnamomum camphora seedlings. The relationships between seedling growth and soil properties were also explored. The results showed that low concentrations of PE-MPs (not larger than 0.5 % in soils) did not restrain seedling growth, while the PE-MP concentrations of 1 % and 2 % decreased the net growth of ground diameter by 38.8 % (p < 0.05) and biomass by 29.6 % (p < 0.05), respectively. Similarly, the concentration of PE-MPs in soils not larger than 0.5 % showed little effect on soil physical properties, while the 1 % and 2 % MP accumulations decreased the soil capillary porosity by 8.9 % and 22.2 % (p < 0.05), respectively, thereby reducing the soil water content by 29.8 % (p < 0.05) and 34.1 % (p < 0.05) accordingly. Furthermore, high concentrations of PE-MPs (1 % and 2 %) greatly decreased soil alkali-hydrolysable nitrogen content and decreased bacterial diversity. The structural equation model clearly indicated that the inhibitory effect of soil PE-MPs with high concentrations on seedling growth was mainly derived from the decrement of soil water holding capacity. Our findings help replenish the regulation mechanism of MPs on plant growth and suggest that C. camphora is a potentially good candidate for the phytoremediation of the low-level PE-MP-contaminated soil.